Job displacement and sectoral mobility - Osborne Jackson (Federal Reserve Bank of Boston, 2021)
This paper combines two components of the US Current Population Survey to characterize the relationship between job displacement and sectoral mobility for long-tenured workers over the 1996-2019 period: (1) the cross-sectional Displaced Worker Survey and (2) the 16-month longitudinal design of the Basic Monthly Survey. While displacement negatively correlates with mobility over time, such job loss has a positive causal impact on mobility for displaced workers compared with similar non-displaced workers. Education and industry structure facilitate post-displacement industry switching, and several factors, including business cycles, affect whether the alternative to sectoral mobility is likely to be sameindustry employment or nonemployment.
Keywords: J63; J24; 330; job displacement; sectoral mobility; Current Population Survey; Displaced WorkerSurvey